2006
DOI: 10.1242/dev.02607
|View full text |Cite
|
Sign up to set email alerts
|

Developmental patterning of the cardiac atrioventricular canal by Notch and Hairy-related transcription factors

Abstract: Mutations in Notch2, Jagged1 or homologs of the Hairy-related transcriptional repressor Hey2 cause congenital malformations involving the non-chamber atrioventricular canal (AVC) and inner curvature (IC) regions of the heart, but the underlying mechanisms have not been investigated. By manipulating signaling directly within the developing chick heart, we demonstrated that Notch2, Hey1 and Hey2 initiate a signaling cascade that delimits the non-chamber AVC and IC regions. Specifically, misactivation of Notch2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 82 publications
8
139
1
Order By: Relevance
“…Our present study shows that alterations of cardiomyocyte proliferative growth develop in grl mutant hearts. Additionally, Hairy-related transcription factors are involved in patterning the atrioventricular canal (28,29). These data suggest that cellular derangements in combination with patterning defects may underlie the morphologic alterations in these malformed hearts and potentially provide a cellular basis for some forms of congenital heart disease.…”
Section: Discussionmentioning
confidence: 93%
“…Our present study shows that alterations of cardiomyocyte proliferative growth develop in grl mutant hearts. Additionally, Hairy-related transcription factors are involved in patterning the atrioventricular canal (28,29). These data suggest that cellular derangements in combination with patterning defects may underlie the morphologic alterations in these malformed hearts and potentially provide a cellular basis for some forms of congenital heart disease.…”
Section: Discussionmentioning
confidence: 93%
“…This might be explained by the downregulation of Hes1 and, more importantly, Hey2, an inhibitor of Bmp2 gene expression during AVC development. 33 Notch signaling thus may inhibit Bmp2 expression in the proepicardium thereby repressing its differentiation into muscle and establishing a posterior border for myocardial differentiation in the SV.…”
Section: Notch Signaling Inactivation Alters CI Differentiation By Inmentioning
confidence: 99%
“…It was first observed that Hey-induced EMT was required in the developing heart (26)(27)(28)(29). Subsequently, Hey proteins were found to be involved in tumor metastasis progression.…”
Section: The Roles Of Hey Proteins In Cancer Metastasismentioning
confidence: 99%